2022
DOI: 10.1051/sicotj/2022046
|View full text |Cite
|
Sign up to set email alerts
|

Operative stabilisation versus non-operative management of mid-shaft clavicle fractures

Abstract: Introduction: Fractures of the mid-shaft clavicle are commonly encountered in clinical practice. These can be managed either by conservative method or operative by internal fixation. This study aims to compare the outcomes of conservative and operative management. Methods: Forty patients with displaced and comminuted mid-shaft clavicle fractures were included in the study, among which twenty-five patients were treated conservatively and 15 patients underwent surgery and were followed up for a period of 1 year.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…The main reason for the unpopularity of these other devices is removal of the implant after fracture union. Several authors have reported on the functional outcomes of both operative and non-operative management of ADMCFs [ 12 , 13 , 14 , 15 , 16 ]. However, the literature has failed to conclusively demonstrate the best indication for these injuries.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for the unpopularity of these other devices is removal of the implant after fracture union. Several authors have reported on the functional outcomes of both operative and non-operative management of ADMCFs [ 12 , 13 , 14 , 15 , 16 ]. However, the literature has failed to conclusively demonstrate the best indication for these injuries.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] To industrially transform commodity thermoplastic into vitrimers the chemistry of vitrimers has to make them processable like traditional thermoplastic without considerable impact on production speed or without the need to change current processing equipment. [ 15,21 ] Therefore, the majority of research around thermoplastic vitrimers have focused on improving and developing dynamic covalent chemistries with tunable reactivity. [ 13 ] However, there are still gaps to be filled to fully understand the implications of the dynamic cross‐links and cross‐linking density in the final part properties, specifically in thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%